Phase‐contrast helium‐3 MRI of aerosol deposition in human airways. (5th December 2014) - Sarracanie, Mathieu; Grebenkov, Denis; Sandeau, Julien; Coulibaly, Soulé; Martin, Andrew R.; Hill, Kyle; Pérez Sánchez, José Manuel; Fodil, Redouane; Martin, Lionel; Durand, Emmanuel; Caillibotte, Georges; Isabey, Daniel; et al.
<x xml:space="preserve">Abstract</x> One of the key challenges in the study of health‐related aerosols is predicting and monitoring sites of particle deposition in the respiratory tract. The potential health risks of ambient exposure to environmental or workplace aerosols and the beneficial effects of medical aerosols are strongly influenced by the site of aerosol deposition along the respiratory tract. Nuclear medicine is the only current modality that combines quantification and regional localization of aerosol deposition, and this technique remains limited by its spatial and temporal resolutions and by patient exposure to radiation. Recent work in MRI has shed light on techniques to quantify micro‐sized magnetic particles in living bodies by the measurement of associated static magnetic field variations. With regard to lung MRI, hyperpolarized helium‐3 may be used as a tracer gas to compensate for the lack of MR signal in the airways, so as to allow assessment of pulmonary function and morphology. The extrathoracic region of the human respiratory system plays a critical role in determining aerosol deposition patterns, as it acts as a filter upstream from the lungs. In the present work, aerosol deposition in a mouth–throat phantom was measured using helium‐3 MRI and compared with single‐photon emission computed tomography. By providing high sensitivity with high spatial and temporal resolutions, phase‐contrast helium‐3 MRI offers new insights for the study of particle transport and deposition. Copyright © 2014 John Wiley & Sons, Ltd.